Paleopathological analysis of a probable case of Jarcho-Levin Syndrome from the 18th century northern Italy - Traversari, Mirko; Figus, Carla; Petrella, Enrico; Piciucchi, Sara; Vazzana, Antonino; Cilli, Elisabetta; Saragoni, Luca; Benazzi, Stefano (Medicina Historica, 2019)
This case report examines the differential diagnosis of an unusually fused chest belonging to a perinatal human remain retrieved in the crypt of Roccapelago (Italy). This specimen, which dated back to the final 18th century, showed a severe synostosis of the costovertebral articulations and posterior arches. The specimen was examined macroscopically and radiologically for the purpose of identify differences in mineral density. It also underwent computed tomography scan in order to create a 3D digital model and virtually reposition in anatomical position. The radiological trophism, size, and osteological maturity of the specimen are compatible with a perinate. The chest structure shows a characteristic crab like morphology, with the costovertebral articulations and some posterior arches completely fused. Accordingly, a diagnosis of Jarcho-Levin Syndrome has been suggested. This case appears to be the first report, to the knowledge of the authors, of a probable Jarcho-Levin syndrome, which dated before Jarcho and Levin codified this pathology in the scientific literature.